1998
DOI: 10.1038/sj.leu.2401017
|View full text |Cite
|
Sign up to set email alerts
|

Ten novel 11q23 chromosomal partner sites

Abstract: The MLL gene located at 11q23 has been described as a 'promiscuous' gene due its involvement with a large number of genetic partners. The EU Concerted Action Workshop on 11q23 provided 550 cases for study of which 82 showed abnormalities which did not involve the established translocations or deletion of 11q23. In these 'other' cases, which included inversions and duplications, 11q23 was found to be involved with 25 chromosome partners of which 10 had not been previously reported. These were 1q31, 4p11, 6q13, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…68,69 More than 54 different partner chromosome regions have now been identified, of which at least 37 partner genes are known (Table 4). 4,70 The t(4;11)(q21;q23) and t(11;19)(q23;p13.3) are the most common translocations in ALL, whereas t(6;11)(q27;q23), t(9;11)(p21-p22;q23), t(10;11)(p12;q23), and t(11;19)(q23;p13.1) are most frequent in AML. [71][72][73][74][75][76] The MLL gene is the human homologue of the Drosophila trithorax gene.…”
Section: Translocations Involving the Mll Gene (11q23)mentioning
confidence: 99%
“…68,69 More than 54 different partner chromosome regions have now been identified, of which at least 37 partner genes are known (Table 4). 4,70 The t(4;11)(q21;q23) and t(11;19)(q23;p13.3) are the most common translocations in ALL, whereas t(6;11)(q27;q23), t(9;11)(p21-p22;q23), t(10;11)(p12;q23), and t(11;19)(q23;p13.1) are most frequent in AML. [71][72][73][74][75][76] The MLL gene is the human homologue of the Drosophila trithorax gene.…”
Section: Translocations Involving the Mll Gene (11q23)mentioning
confidence: 99%
“…[1][2][3][4] At least 40 different partner chromosomes have been involved in 11q23 translocations. [5][6][7][8][9][10][11][12] To date, 13 genes involved in translocations with MLL have been cloned. [13][14][15][16][17][18][19][20][21][22][23][24][25] It has been suggested that alteration of the MLL protein is the critical event in oncogenesis and that fusion partners may not play an important role in the oncogenic process.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the case of a 48-year-old man with no previous history of toxic exposure, su ering from AML-M4, which was cytogenetically characterized as 46,XY,-3, t(11;15)(q23;q14), +mar (Archimbaud et al, 1998;Harrison et al, 1998). The bone marrow was hypercellular, with 80% blast cells.…”
mentioning
confidence: 99%